The effect of the higher education qualifications sub-framework act on the academic organisational structure of a university of technology - Kapp, K.; du Plessis, A. (South African Journal of Higher Education, 2025)
Phasing out existing qualifications and phasing in new ones on a large scale is a costly exercise in any institution of higher education. This research aimed to determine how the implementation of the Higher Education Qualification Sub-Framework (HEQSF) Act would affect the academic organisational structure at a university of technology and to develop an instrument to manage the phasing in and phasing out of qualifications on a large scale in a sustainable way. The pragmatic paradigm underpinned this mixed method study and the National Implementation Research Network Framework (NIRN) and Complexity Theory framed this research. The primary aim of this study was to develop a framework that predicts how the phasing in/phasing out of programmes of a faculty will affect the workload of academic staff and subsequently the academic organisational structure of the institution. Such a tool will enable each faculty at the selected university to accurately predict the quantity of additional human resources needed during this process of phasing in and phasing out of new and old programmes while ensuring financial sustainability at the institution. This will enable the university to determine human resource requirements and student enrolments and to align them with the university’s targeted budget allocation.